Vestibular migraine management by the United Kingdom ear, nose and throat clinicians: a “snapshot” - Munnings, Amberley; Moualed, Daniel (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Vestibular migraine is a common cause of dizziness with various management options, similar to that of regular migraine treatments. This study aimed to characterise current practice in vestibular migraine (VM) management amongst ear, nose and throat (ENT) specialists across the United Kingdom (UK). Methods: A national survey of ENT UK members regarding their management of VM was conducted. Freedom of information requests were also sent to each integrated health board (IHB) to determine if they had a migraine and/or vestibular migraine protocols. Results: There was wide variability across ENT clinicians in their management of VM with 45.29% starting no treatment or lifestyle advice only before transferring the care of the patient to another provider. Only 4 IHBs had a migraine protocol that referenced VM. Conclusions: This study identifies the variation in the management of vestibular migraine across ENT clinicians. It also potentially highlights the need for improved education of ENT trainees about the condition. The authors would support ENT clinicians to become involved in writing migraine protocols for their trusts, to include vestibular migraine within these guidelines.